A type of cylindrical Hall thruster with a magnetically insulated anode. (8th March 2017) - Yongjie, Ding; Yu, Xu; Wuji, Peng; Liqiu, Wei; Hongbo, Su; Hezhi, Sun; Peng, Li; Hong, Li; Daren, Yu
Abstract: In this paper, a type of magnetically insulated anode structure is proposed for the design of a low-power cylindrical Hall thruster. The magnetic field distribution in the channel is guided by the magnetically insulated anode, altering the intersection status of the magnetic field line passing through the anode and wall. Experimental and simulation results show that a high potential is formed near the wall by the magnetically insulated anode. As the ionization moves towards the outlet, the energy and flux of the ions bombarding the channel wall can be reduced effectively. Due to the reduction in the bombardment of the wall from high-energy ions, the thrust and specific impulse greatly increase compared with those of the non-magnetically insulated anode. For anode mass flow rates of 0.3 and 0.35 mg s −1 and discharge voltages in the 100–200 V range, the thrust can be increased by more than 33% and the anode efficiency can be improved by more than 7%. Meanwhile, the length of the sputtering area is clearly reduced. The starting position of the sputtering area is in front of the magnetic pole, which can effectively prolong the service life of the thruster.